The Validity of Wiretapping as Evidence in Corruption Cases - Cahyono, Denzel Andersson; Lie, Gunardi (GoAcademica Research & Publishing, 2024)
Corruption crimes committed by state officials in Indonesia are rampant. Therefore, the Corruption Eradication Commission (KPK), as an independent institution, has a heavy-duty to investigate the perpetrators of Corruption Crimes in Indonesia. Of course, the KPK in the trial requires strong evidence to reveal the perpetrators of special crimes, namely corruption. With this evidence, the KPK will be able to prove that the perpetrator is proven to have committed the crime of corruption It is known that the KPK Law has just been revised, Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission. Where there are changes in procedures listed in the new law. This refers to how the KPK can conduct wiretapping and obtain official permission to wiretap perpetrators who are indicated to have committed corruption crimes.